PERBEDAAN HASIL BELAJAR PRAKTIKUM CETAK SARING YAN MENGGUNAKAN METODE KERJA KELOMPOK DENGAN PEMBERIAN TUGAS INDIVIDU PADA SISWA KRIYA TEKSTIL SMKN 4 PADANG - Aminur Miswah, Drs. Eswendi, M.Pd., Drs. Wisdiarman, M.Pd. (Universitas Negeri Padang, 2016)
The purpose of this study was to examine differences in learning outcomes practicum screen printing between ( 1 ) a method of group work by giving individual assignments in SMKN 4 Padang, ( 2 ) group work method with the conventional method in SMKN 4 Padang, ( 3 ) the provision of individual tasks with methods conventional SMKN 4 Padang. Samples were students of class XI Textile Craft SMKN 4 Padang taken by purposive sampling technique. Data collected by using the performance test. The findings of the study are ( 1 ) There are differences in learning outcomes between methods practicum Screen Printing group work by giving individual assignments at the Department of Textile Craft SMKN 4 Padang. ( 2 ) There are differences in learning outcomes between the Screen Printing lab group work method with conventional methods SMKN 4 Padang. ( 3 ) There is no difference in learning outcomes between the administration practicum Screen Printing individual tasks to conventional methods in SMKN 4 Padang.Kata kunci: metode kerja kelopok, pemberian tugas